The impact of russian aggression on the air component of the environment - Kharchenko, Viacheslav; Rudyk, Bohdan (My University, 2025)
The damage caused to the air in Ukraine as a result of Russian war crimes currently exceeds EUR 16 billion. Air is the most dynamic component of ecosystems. Therefore, damage to it leads to rapid negative consequences for the ecosystem as a whole and for human health. Russia’s war crimes continue. They need to be stopped and the damage caused must be fully compensated. For Ukraine to meet both of these goals, international support is essential. Шкода, завдана повітрю в Україні внаслідок воєнних злочинів Росії, наразі перевищує 16 млрд євро. Повітря є найдинамічнішим компонентом екосистем. Тому пошкодження його призводить до швидких негативних наслідків для екосистеми в цілому та для здоров'я людини. Військові злочини Росії тривають. Їх потрібно зупинити, а завдану шкоду повністю відшкодувати. Для того, щоб Україна досягла обох цих цілей, міжнародна підтримка є надзвичайно важливою.
Keywords: russian aggression; impact on the air component; environment; російська агресія; вплив на повітряний компонент; довкілля; кафедра екології та екоменеджменту